Multicultural education management in Indonesian Language learning for foreign students in Indonesia - Koeswanti, Henny Dewi (Universitas Pendidikan Ganesha, 2019)
The purpose of Indonesian language learning for BIPA (Indonesian Language Learning for Foreign Speakers) students emphasizes the involvement/participation of students in the learning process. This study contains 1) the nature of educational management for foreign students studying in Indonesia; 2) implementation of educational management in Indonesian language learning for foreign speakers (BIPA); 3) Indonesian language learning plans for BIPA students; and 4) the implementation of Indonesian language learning for BIPA students based on the introduction of Indonesian culture. Data collection techniques in this study use observation, document analysis, interviews and documentation techniques. Then, data analysis techniques are carried out by means of data collection, data reduction, data presentation and conclusion drawing. The management of education for BIPA students is different from the management of education for Indonesian students because BIPA students consist of various cultures and different countries. The implementation of education management must also be included in the semester implementation plan (RPS), learning syllabus, and learning evaluation in the BIPA class. Learning plans in the BIPA class are also important to highlight because they will present facts that are different from the language learning plan in the regular class. The results of this study are highlights and ideas in educational management and Indonesian language learning in the BIPA program. This can be implemented in Indonesian language learning for foreign students in the BIPA class to be more effective based on the introduction of Indonesian culture because foreign students will be enthusiastic and interested in Indonesia's rich and diverse cultural products. The implication of the idea in this article is that it can be used as a reference material in the implementation of BIPA program educational management and provide insight and reinforcement about the role of Indonesian culture as a supporting tool in the learning process in the BIPA program.